Autogation: An Alternate Wetting and Drying-Based Automatic Irrigation and Paddy Water Level Control System through Internet of Things - Tolentino, Lean Karlo S.; Bacaltos, Patrick Carlos; Cruz, Rica Mikaela V.; Dela Cruz, Neal Jhon S.; Medina, Leah Ruth S.; Panergalin, John Vincent; Padilla, Maria Victoria C.; Velasco, Jessica S. (AGRIVITA, Journal of Agricultural Science, 2021)
This study aims to create an automated watering system that can adapt with network-based irrigation monitoring and a safe alternate wetting and drying or AWD. A secure AWD irrigation method is one in which the rice paddy is alternately subsided and immersed with a critical level of 100mm below the ground and a maximum irrigation level of 150 mm above the ground. The designed methodology automates irrigation by considering the needed water level in the field and its present level. It determines and controls the watering schedule based on the data collected by the sensors and then acts on it. It regulates the irrigation delivery gate to close or open the counterweight-designed water gate valve following the smart timetable that it has established. This approach conserved around 20% of the water used in a two-hectare area with four weirs compared to the traditional irrigation method in three weeks.